Mathematical and statistical applications in food engineering - Sevda, Surajbhan, 1985-; Singh, Anoop (Scientist) (Boca Raton : CRC Press ; Taylor & Francis Group, 2020)
Written by experts from all over the world, the book comprises the latest applications of mathematical and models in food engineering and fermentation. It provides the fundamentals on statistical methods to solve standard problems associated with food engineering and fermentation technology. Combining theory with a practical, hands-on approach, this book covers key aspects of food engineering. Presenting cuttingedge information, the book is an essential reference on the fundamental concepts associated with food engineering.
OCLC-licensed vendor bibliographic record.
Keywords: Food industry and trade -- Mathematical models; Food industry and trade -- Statistical methods; MATHEMATICS / Applied; SCIENCE / Life Sciences / General; TECHNOLOGY / Food Science